2017
DOI: 10.4236/ajps.2017.86079
|View full text |Cite
|
Sign up to set email alerts
|

DNA Markers for Selection of Late Blight Resistant Potato Breeding Lines

Abstract: Potato late blight, caused by the oomycete Phytophthora infestans, is one of the most devastating diseases in the agricultural sector around the world. Many genes (R genes) conferring resistance to late blight have been identified in various potato species and most of these R genes have been used in potato breeding. The aim of this study was to develop and validate PCR-based assays for the R genes Rpi-blb1, Rpi-blb2, Rpi-blb3 and Rpi-bt1, to distinguish between late blight resistant and late blight susceptible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…Presence of Rpi-blb1 late blight resistant gene was shown in lines 13, 41, 61, 72, 54 and 70. Similar findings were reported by Chen et al [16], who stated that genotypic and phenotypic data were related in case of late blight disease when DNA markers derived from the Rpi-blb1 gene were used for marker assisted selection. However, from these findings it is revealed that, late blight resistant gene had been successfully transferred to the recipient variety from the donor, in most of the selected LB resistant lines.…”
Section: Late Blight Gene Confirmationsupporting
confidence: 88%
See 1 more Smart Citation
“…Presence of Rpi-blb1 late blight resistant gene was shown in lines 13, 41, 61, 72, 54 and 70. Similar findings were reported by Chen et al [16], who stated that genotypic and phenotypic data were related in case of late blight disease when DNA markers derived from the Rpi-blb1 gene were used for marker assisted selection. However, from these findings it is revealed that, late blight resistant gene had been successfully transferred to the recipient variety from the donor, in most of the selected LB resistant lines.…”
Section: Late Blight Gene Confirmationsupporting
confidence: 88%
“…DNA was isolated from sprout by following CTAB method [15]. PCR was performed with selected markers [16]. Amplified PCR products were detected on a 3% agarose gel stained in 1 x Tris-base EDTA buffer and visualised on a UV trans-illuminator.…”
Section: Lb Gene Confirmation Through Pcrmentioning
confidence: 99%
“…Despite a wide range of genetic studies of the potato tubers eye depth trait and the identification of genes and QTL associated with eye depth variability, DNA markers are still not used in the breeding of potatoes to this trait. Meanwhile, the use of diagnostic DNA markers allows to carry out more efficient prebreeding research (screening of potato genetic resources to identify donors of valuable allelic variants) and markerassisted selection in breeding programs (Gebhardt et al, 2006;Chen et al, 2017;Klimenko et al, 2017Klimenko et al, , 2019. We were able to develop a number of new PCR markers that can be convenient for screening the genetic resources and breeding material of potato.…”
Section: Resultsmentioning
confidence: 99%
“…The genes R1, R2 and its orthologue Rpi-abpt, R2-like, and Rpi-blb3; R3a and R3b, R8, R9a, the orthologues Rpi-blb1 and Rpi-sto1, Rpi-blb2, Rpi-vnt1 and Rpi-chc1 have been located on chromosomes 4 to 11 and characterized most comprehensively [11]. DNA markers corresponding to the fragments of Rpi genes introgressed into cultivated potato from wild relatives are actively deployed for screening breeding material to select promising genotypes combining several Rpi genes [12][13][14]. The dRenSeq method for diagnostic sequencing genome target fragments ensures a high degree of certainty of the identification of full-length sequences of known Rpi genes in genetic collections and breeding material [15].…”
Section: Introductionmentioning
confidence: 99%